Increased efficacy and extended shelf life of spinosad formulated in phagostimulant granules against Spodoptera frugiperda - Tamez Guerra, Patricia; Tamayo Mejía, Fernando; Gómez Flores, Ricardo Alberto; Rodríguez Padilla, Cristina; Damas, Gabriela; Tamez Guerra, Reyes Silvestre; Ek Ramos, María Julissa; Williams, Trevor (2017)
Abstract BACKGROUND:SpinosadisrecommendedforcontrolofSpodopterafrugiperda(J.E.Smith)larvae;itsapplicationwithphagostimulants may reduce the quantity of active ingredient required for eﬀective pest control. Spinosad (Tracer®) was formulated inmaizeﬂourmatrixgranulesandthreeﬁeldtestscompared10–100ppma.i.granules(equivalentto0.24–2.4ga.i.ha–1)with Tracerasanaqueousspray(200ppma.i.;60ga.i.ha–1),andtherecommendedapplicationratesofBacillusthuringiensis,achemicalandanuntreatedcontrolswereperformed. RESULTS:The100ppmspinosadgranulesresultedinsimilarS.frugiperdamortalitycomparedwiththechemicaltreatmentsin allthreeﬁeldtrials,andresultedinasigniﬁcantlyhighermaizegrainyieldcomparedwithunformulatedandcontroltreatments (4141vs.2857and2407kgha–1,respectively)thatwassimilartothechemicaltreatment(3778kgha–1).Bioassaysofgranules stored at room and cold temperatures showed that after 5years, ∼ 70% of the original activity remained (OAR) of spinosad whenformulatedasgranules.Nevertheless,after9years,eﬃcacywasreduced(26.2%and48.5%OAR)atbothroom(25∘C)and refrigeratedtemperatures(4∘C). CONCLUSION:Spinosad,inthegranularphagostimulantformulationsevaluatedinthisstudy,hadadvantagesmeasuredashigh eﬃcacyandlongshelflife.